2018
DOI: 10.1111/jcmm.13529
|View full text |Cite
|
Sign up to set email alerts
|

MiR‐129‐5p inhibits glioma cell progression in vitro and in vivo by targeting TGIF2

Abstract: This study purposed to explore the correlation between miR‐129‐5p and TGIF2 and their impacts on glioma cell progression. Differentially expressed miRNA was screened through microarray analysis. MiR‐129‐5p expression levels in glioma tissues and cells were measured by qRT‐PCR. CCK‐8 assay, flow cytometer, transwell assay and wound‐healing assay were employed to detect cell proliferation, apoptosis and cycle, invasiveness and migration, respectively. Dual‐luciferase reporting assay was performed to confirm the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 27 publications
2
21
0
Order By: Relevance
“…Literature so far suggests the dual nature of TGIF2 where it may function as a tumor suppressor or as an oncogene . Also, in line with our observation, TGIF2 was shown to promote aggressive phenotype in gliomas . Interestingly, some studies have reported TGF‐β signaling to have a context‐dependent role which could also be mediated via TGIF2 induced singling .…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Literature so far suggests the dual nature of TGIF2 where it may function as a tumor suppressor or as an oncogene . Also, in line with our observation, TGIF2 was shown to promote aggressive phenotype in gliomas . Interestingly, some studies have reported TGF‐β signaling to have a context‐dependent role which could also be mediated via TGIF2 induced singling .…”
Section: Discussionsupporting
confidence: 87%
“…[36][37][38] Also, in line with our observation, TGIF2 was shown to promote aggressive phenotype in gliomas. 39 Interestingly, some studies have reported TGF-β signaling to have a context-dependent role which could also be mediated via TGIF2 induced singling. 40 Our TCGA data analysis showed TGIF2 to exhibit an inverse correlation with both miR-490-3p as well as CHRM2 in GBM patient samples thereby adding to its significance in gliomas.…”
Section: Discussionmentioning
confidence: 99%
“…MiR‐129 is a recently discovered tumour‐associated miRNA found to be dysregulated in cancers. Diao et al demonstrated that miR‐129 combined with TGIF2 could disturb glioma progression. In the case of glioblastoma multiforme, miR‐129 blocked the ability of cell proliferation, invasion, migration, neurosphere formation, angiogenesis and temozolomide resistance via Wnt5a by blocking the PKC/ERK/NF‐κB and JNK pathways .…”
Section: Introductionmentioning
confidence: 99%
“…TGIF2 has been identified as an oncogene in some cancers, such as lung adenocarcinoma [30] and glioma [31]. In OS, TGIF2 has also been reported to be involved in tumor progression [32].…”
Section: Discussionmentioning
confidence: 99%